Social Problems and Women´s Politics in Eastern Europe - Socialist, Feminist and Neo-Liberal Perspectives - Sabine Hering (Social Work & Society, 2011)
The post-1989 transition from state socialism to capitalism and democracy has produced winners and losers. There is no doubt that women in Eastern Europe find themselves mainly among the loser. Irrespective of variations in economic and political development, birth-rates dramatically dropped in all countries of the former 'Eastern Bloc', while at the same time female unemployment increased significantly. Statistics disclose the reasons behind this development. They reveal a sharp decline in the number of places available in day nurseries for children, and an escalation of gender-specific segregation in the labour market. Both developments have contributed to a 'feminisation of poverty' which many Eastern European authorities accept as an inevitable consequence of modernisation.